2021
DOI: 10.1177/23800844211028541
|View full text |Cite
|
Sign up to set email alerts
|

Dental Visits during Pregnancy: Pregnancy Risk Assessment Monitoring System Analysis 2012–2015

Abstract: Objectives: This study aimed to update dental service utilization during pregnancy and to evaluate whether there are persistent disparities in dental care during pregnancy by race/ethnicity and Medicaid status. Methods: This retrospective secondary data analysis examined dental service utilization during and prior to pregnancy and met dental or oral health needs using the Pregnancy Risk Assessment Monitoring System (PRAMS) data sets on 75,876 women between 2012 and 2015. Results: Only about half of the women (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
(42 reference statements)
0
18
0
Order By: Relevance
“…It is, however, an overlooked element among public health interventions. Untreated dental caries in pregnant women can lead to higher risk for dental caries in young children through vertical transmission of cariogenic bacteria [ 5 , 6 ]. Severe early childhood caries can lead to extensive dental treatment under sedation, impairing everyday functions, such as speech and nutrition [ 5 ].…”
Section: Why Is Maternal Oral Health Important?mentioning
confidence: 99%
See 1 more Smart Citation
“…It is, however, an overlooked element among public health interventions. Untreated dental caries in pregnant women can lead to higher risk for dental caries in young children through vertical transmission of cariogenic bacteria [ 5 , 6 ]. Severe early childhood caries can lead to extensive dental treatment under sedation, impairing everyday functions, such as speech and nutrition [ 5 ].…”
Section: Why Is Maternal Oral Health Important?mentioning
confidence: 99%
“…Untreated dental caries in pregnant women can lead to higher risk for dental caries in young children through vertical transmission of cariogenic bacteria [ 5 , 6 ]. Severe early childhood caries can lead to extensive dental treatment under sedation, impairing everyday functions, such as speech and nutrition [ 5 ]. Research has shown a positive association between periodontal disease during pregnancy and adverse birth outcomes, such as low birth weight and preterm birth [ 7 , 8 ], even though there are mixed results on the association of periodontal treatment and reduced adverse birth outcomes [ 9 ].…”
Section: Why Is Maternal Oral Health Important?mentioning
confidence: 99%
“…During pregnancy, women are at increased risk of oral disease due to hormonal changes and behavioral changes [ 2 , 3 , 4 ]. Unfortunately, those women most vulnerable to oral disease (racial–ethnic minorities, low-income women) have the lowest rates of dental utilization during pregnancy [ 13 , 14 , 15 ]. Importantly, for these vulnerable women, pregnancy may be the only time when they have coverage for dental care via the Medicaid program, as is the case in New York State [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, the New York State Department of Health published a set of evidence-based guidelines that advocate for the provision of preventive dental care and timely treatment of dental disease during pregnancy [ 9 ]. Despite these and other guidelines [ 10 ], and the overwhelming evidence that dental care during pregnancy is safe and effective [ 11 , 12 ], utilization of dental services among pregnant women has remained low, especially among low-income women [ 13 , 14 , 15 , 16 ]. To date, there are few reports of successful evidence-based programs designed to improve dental care utilization among pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue, readers will find 2 reports on oral health in pregnancy. Lee Het al (2022) analyzed data from >75,000 pregnant women from the 2012–2015 US Pregnancy Risk Assessment Monitoring System; they found that only slightly more than half had seen a dentist for a cleaning during their pregnancy, with non-Hispanic Black and Hispanic women significantly less likely than White women to have done so. When compared with those with private insurance, women enrolled in Medicaid were significantly less likely to have had a dental cleaning during their pregnancies.…”
mentioning
confidence: 99%